FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PARTISIPASI PRIA DALAM KELUARGA BERENCANA DI KECAMATAN RUMBAI PESISIR TAHUN 2012 - YESSI HARNANI (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2015)
The man participation in family planning (FP) mean to take part in this program inspite of founding good sexual behavior for themselves and their wife. This research explore several factors which related to man participation in FP program on Rumbai Pesisir Sub district, Municipality of Pekanbaru in the year of 2012.Research design is case control study, with case is the man not participate in FP program while as control is the man whom taking part on the FP in the year of 2012. Result the man with acces difficulty to family planning program 10 times risk not to participate compared with the counterpart/control (CI 95% : OR = 5,3 – 17,9), men not supported by social and cultural aspect for family planning program 4 times risk not to participate (CI 95% : OR= 2,4 – 7,9), men with negative opinion to family palnning program 4 times risk not to participate(CI 95%: OR = 1,3 – 7,0), while the man from low income family 2 times risk not to participate (CI 95% : OR = 1,2 – 3,5) compared with their counterparts respectively. Conclusion: Multivariate analysis revealed that independent variable related to man participation , the family planning program, social and cultural aspect, opinión to family planning program and family income. Wife age is the only Independence variabel related counter directionally. Parity, education level and knowladge to family planning program are three variables not related to men participation, meanwhile family planning service quality is the confounding variable to service acces variable and social and cultural variable. Suggestion : increase quality and acces of family planning services including site of service, concellor, cost and spesific family planning promotion for mankind. Family planning and health service program is distributed to all area of Rumbai Pesisir subsdistric and to increase the support of public figure and all stake holder for Family planning program.